Physicochemical characteristics of soluble oligomeric A β and their pathologic role in Alzheimer's disease - Watson, Desiree (2013)
Extracellular fibrillar amyloid deposits are prominent and universal Alzheimer's disease (AD) features, but senile plaque abundance does not always correlate directly with the degree of dementia exhibited by AD patients. The mechanism(s) and dynamics of Abeta fibril genesis and deposition remain obscure. Enhanced Abeta synthesis rates coupled with decreased degradative enzyme production and accumulating physical modifications that dampen proteolysis may all enhance amyloid deposit formation. Amyloid accumulation may indirectly exert the greatest pathologic effect on the brain vasculature by destroying smooth muscle cells and creating a cascade of negative impacts on cerebral blood flow. The most visible manifestation of amyloid dis-equilibrium could actually be a defense mechanism employed to avoid serious vascular wall degradation while the major toxic effects to the gray and white matter neurons are mediated by soluble oligomeric Abeta peptides with high beta-sheet content. The recognition that dynamic soluble oligomeric Abeta pools exist in AD and are correlated to disease severity led to neurotoxicity and physical conformation studies. It is now recognized that the most basic soluble Abeta peptides are stable dimers with hydrophobic regions sequestered from the aqueous environment and are capable of higher order aggregations. Time course experiments employing a modified ELISA method able to detect Abeta oligomers revealed dynamic intermolecular interactions and additional experiments physically confirmed the presence of stable amyloid multimers. Amyloid peptides that are rich in beta-sheet structure are capable of creating toxic membrane ion channels and a capacity to self-assemble as annular structures was confirmed in vitro using atomic force microscopy. Biochemical studies have established that soluble Abeta peptides perturb metabolic processes, provoke release of deleterious reactive compounds, reduce blood flow, induce mitochondrial apoptotic toxicity and inhibit angiogenesis. While there is no question that gross amyloid deposition does contribute to AD pathology, the destructive potential now associated with soluble Abeta suggests that treatment strategies that target these molecules may be efficacious in preventing some of the devastating effects of AD.